Melatonin Alleviated Potassium Dichromate-Induced Oxidative Stress and Reprotoxicity in Male Rats. (16th June 2021) - Bashandy, Samir A. E.; Ebaid, Hossam; Al-Tamimi, Jameel; Ahmed-Farid, Omar A.-H.; Omara, Enayat A.; Alhazza, Ibrahim M.
Abstract : Melatonin (ML) is a potent antioxidant that reduces oxidative stress. This study was designed to examine the protective effect of melatonin on potassium dichromate- (PDC-) induced male reproductive toxicity. Forty rats were divided into five groups: the control group, rats administered PDC orally (10 mg/kg body weight) for eight weeks, rats administered ML intraperitoneally at doses of either 2.5 or 5 mg/kg followed by the administration of PDC, and rats administered 5 mg/kg ML only. The treatment of rats with PDC led to a decrease in the levels of plasma sex hormones, glutathione, superoxide dismutase, catalase, carnitine, sperm count, and motility. Testicular malondialdehyde levels, nitric oxide concentrations, and abnormalities increased significantly in the PDC group. Melatonin administration to the PDC-treated rats reduced the increase of malondialdehyde and restored the activity of antioxidant enzymes (superoxide dismutase and catalase), glutathione, and sex hormone levels. Moreover, ML attenuated PDC-induced increase in levels of tumor necrosis factor-alpha or interleukin-6. ML alleviated histopathological changes and an increase of p53-positive immune reaction due to PDC. Furthermore, ML inhibited PDC-induced decrease in the DNA content of spermatogenic cells. This study proposed that melatonin may be useful in mitigating oxidative stress-induced testicular damage due to potassium dichromate toxicity.